2019
DOI: 10.1177/1073858419844497
|View full text |Cite
|
Sign up to set email alerts
|

Synaptotagmins: Beyond Presynaptic Neurotransmitter Release

Abstract: Synaptotagmins (Syts) are well-established primary Ca2+ sensors to initiate presynaptic neurotransmitter release. They also play critical roles in the docking, priming, and fusion steps of exocytosis, as well as the tightly coupled exo-endocytosis, in presynapses. A recent study by Awasthi and others (2019) shows that Syt3 Ca2+-dependently modulates the postsynaptic receptor endocytosis and thereby promotes the long-term depression (LTD) and the decay of long-term potentiation (LTP). This work highlights the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…This result could be explained with the ability of this compound to restore the physiological values of expression of selected proteins. The three proteins taken into consideration, namely Syt 1, Stx 1b and CAMK2A, are notoriously involved in neurotransmitter exocytosis from ready releasable vesicles and in synaptic plasticity [43,44]. The 5-HT pathway has also been considered as cornerstone to explain the antidepressant effects in mice treated with CBD [45].…”
Section: Discussionmentioning
confidence: 99%
“…This result could be explained with the ability of this compound to restore the physiological values of expression of selected proteins. The three proteins taken into consideration, namely Syt 1, Stx 1b and CAMK2A, are notoriously involved in neurotransmitter exocytosis from ready releasable vesicles and in synaptic plasticity [43,44]. The 5-HT pathway has also been considered as cornerstone to explain the antidepressant effects in mice treated with CBD [45].…”
Section: Discussionmentioning
confidence: 99%
“…SYT12 was first described as being homologous to SYT1, which is a thyroid hormone-induced protein [7]. The synaptotagmins, including SYT1, were identified in 1990 [20], and have been established as the primary Ca 2+ sensors for vesicular exocytosis and endocytosis [6]. Mammalian cells contain 17 genes that encode synaptotagmins, and all 17 synaptotagmins have similar molecular structures, but only a minority have been studied in detail [6].…”
Section: Discussionmentioning
confidence: 99%
“…The synaptotagmins, including SYT1, were identified in 1990 [20], and have been established as the primary Ca 2+ sensors for vesicular exocytosis and endocytosis [6]. Mammalian cells contain 17 genes that encode synaptotagmins, and all 17 synaptotagmins have similar molecular structures, but only a minority have been studied in detail [6]. Few previous studies have reported the association between synaptotagmin family members and human cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations